A multi‐Internet service provider game: Equilibrium, stability, and characteristics. (20th February 2020) - Fu, Hong; Chen, Bo; Zhang, Bin
Summary: This paper proposes a multi‐Internet service provider (ISP) game model for investigating the economic interactions among ISPs who compete or cooperate with each other for customers. The equilibrium and stability properties of the multi‐ISP game in different market scenarios, that is, competitive market, collaborative market, mixed market, and winner‐take‐all market, are investigated. Some qualitative and managerial insights into market outcomes are obtained to characterize the set of equilibria. Furthermore, numerical examples are also employed to illustrate the typical characteristics of the multi‐ISP market. The simulation results provide possible explanations for the evolution of the multi‐ISP game. The results also indicate that the constructed model can predict the main characteristics of the Internet service market in different market scenarios.